The Modeling Research on the Early-Age Shrinkage of UHPFRC in Different Curing Conditions - Song Han; Yazhou Liu; Dan Liu; Mingzhe An; Ziruo Yu (Advances in Civil Engineering)
The early-age shrinkage of ultra-high performance fiber reinforced concrete (UHPFRC) in dry, sealed, and soaked curing was systematically measured. The calculation model of early-age shrinkage was established based on the theory of shrinkage of cementitious materials. According to the results of the relative humidity, hydration degree, pore structure, and elastic modulus of hardened slurry, the shrinkage calculation model in different curing conditions was calibrated. The results show that the early-age shrinkage of UHPFRC can be divided into three parts: chemical shrinkage, autogenous shrinkage caused by self-drying, and drying shrinkage caused by external drying. Based on the degree of hydration, the chemical shrinkage model was established. Based on the pore structure, the hydration degree, and the relative humidity of hardened slurry, the autogenous shrinkage model was established by introducing the effective pore coefficient. The drying shrinkage model was established based on the internal humidity. According to the shrinkage of soaked samples, the calculated value of chemical shrinkage in sealed and drying conditions was calibrated. This research provides theoretical support for the structural design and engineering application of UHPFRC.